Effects of various pretreatments of oil palm empty fruit bunch fibres for subsequent use as substrate on the performance of cellulase production by Aspergillus Terreus. - Shahriarinour, Mahdi; Abdul Wahab, Mohd Noor; Ariff, Arbakariya; Mustafa, Shuhaimi; Mohamad, Rosfarizan (North Carolina State University, 2011)
The possibility of using treated oil palm empty fruit bunch (OPEFB) fibres as substrate for cellulase production by Aspergillus terreus was studied using shaking flask fermentation. The effect of different chemical pretreatments, i.e. formic acid, acetic acid, propylamine, phosphoric acid, and n-butylamine, on the suitability of OPEFB fibres as fermentation substrate was investigated. The findings revealed that pretreatment with these chemicals significantly (P<0.05) increased the cellulose and reduced the lignin contents prior to enzymatic hydrolysis. However, fermentation using OPEFB fibres pretreated with phosphoric acid gave the highest cellulase production, which was related to high cellulose content. Further improvement in cellulase production was obtained when the chemically pretreated OPEFB fibres were subsequently treated hydrothermally (autoclaved at 160oC for 10 min) and then biologically (using effective microorganisms). The final activity of the three main components of cellulase (FPase, CMCase, and β-glucosidase) obtained in fermentation by A. terreus using optimally treated OPEFB fibres was (0.77 U mL−1, 8.5 U mL-1, and 6.1 U mL-1), respectively. The production of all these three major components of cellulase using pretreated OPEFB fibres (i.e. chemical, hydrothermal, and biological) were about three times higher than those obtained from fermentation using untreated OPEFB fibres.